Analisa Rasio Keuangan : Earning Per Share, Return On Invesment, Current Rasio, Total Asset Turn Over dan Debt to Equity Rasio terhadap Harga Saham pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Eka Setya Atsari Ramadhan, 14.05.52.0068; Puspitasari, Elen (Students' Journal of Accounting and Banking, 2018)
This study aims to test and analyze the financial ratios of Earning Per Share, Return On Investment, Current Ratios, Total Asset Turn Over and Debt to Equity Ratios on stock prices in manufacturing companies listed on the Indonesia Stock Exchange (IDX). The population in this study are manufacturing companies that have go public on the Indonesia Stock Exchange for the period 2012-2013. The sampling technique in this study is to use purposive sampling. The data analysis technique used is multiple linear regression analysis. Based on the test results it can be concluded that: Earning Per Share has a positive effect on stock prices, Return On Investment has a positive effect on stock prices, Current Ratio has a positive effect on stock prices, Total Asset Turn Over has a negative effect on stock prices, and Debt to Equity Ratio has no effect against stock prices. Keywords: Earning Per Share, Return On Investment, Current Ratio, Total Asset Turn Over and Debt to Equity Ratio.